Animal movements in the Kenya Rift and evidence for the earliest ambush hunting by hominins. - Kübler, Simon; Owenga, Peter; Reynolds, Sally C; Rucina, Stephen M; King, Geoffrey C P (Sci Rep, 2015)
Animal movements in the Kenya Rift Valley today are influenced by a combination of topography and trace nutrient distribution. These patterns would have been the same in the past when hominins inhabited the area. We use this approach to create a landscape reconstruction of Olorgesailie, a key site in the East African Rift with abundant evidence of large-mammal butchery between ~1.2 and ~0.5 Ma BP. The site location in relation to limited animal routes through the area show that hominins were aware of animal movements and used the location for ambush hunting during the Lower to Middle Pleistocene. These features explain the importance of Olorgesailie as a preferred location of repeated hominin activity through multiple changes in climate and local environmental conditions, and provide insights into the cognitive and hunting abilities of Homo erectus while indicating that their activities at the site were aimed at hunting, rather than scavenging.